2006
DOI: 10.1253/circj.70.750
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Inverted T Waves in Patients With Acute Pulmonary Embolism

Abstract: Background The significance of inverted T waves remains unclear in patients with acute pulmonary embolism (PE). Methods and ResultsThe relationship of the number of leads with inverted T waves to the severity of PE in 40 patients with acute PE was studied. Patients were classified into 3 groups according to the number of leads with inverted T waves on the admission electrocardiogram (ECG): 15 patients, ≤3 leads (group L); 12 patients, 4-6 leads (group M); and 13 patients, ≥7 leads (group H). In groups L, M and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 27 publications
2
52
0
2
Order By: Relevance
“…We also speculate [14] and in patients who were not treated for APE [3,5]. More leads with NTW are also related to worse short-term prognosis [18,19]. However, there is a poor relationship in patients after effective treatment where the RVD has possibly been recovered [14,17].…”
Section: Discussionmentioning
confidence: 73%
“…We also speculate [14] and in patients who were not treated for APE [3,5]. More leads with NTW are also related to worse short-term prognosis [18,19]. However, there is a poor relationship in patients after effective treatment where the RVD has possibly been recovered [14,17].…”
Section: Discussionmentioning
confidence: 73%
“…24) Furthermore, an increasing number of leads with T wave inversion was related to a higher mortality rate and a higher frequency of complications. 25,26) A possible mechanism of T wave inversion is acute cor pulmonale with rapid right ventricular pressure overload and right ventricular enlargement, although it is not completely understood. In 44 patients with CTEPH, Lewzcuk, et al reported that a negative T wave in the precordial V1-V5 leads was most commonly observed (45.4%) as an ECG sign of right ventricular overload, and the sensitivity and specificity for detecting MPAP > 30 mmHg were 48.0% and 95.0%, respectively.…”
Section: )mentioning
confidence: 99%
“…reported a significant association between the number of negative T wave leads and the severity of pulmonary thromboembolism 11) . In present case, the number of negative T wave leads on ECG gradually declined from left-to right-sided leads of horizontal plane and leftward to rightward axis of the frontal plane of the heart according to the improvement of right heart overload.…”
Section: ) 5) 7)-9)mentioning
confidence: 99%